FlexiDig – Flexible Digital Classroom : Master students’ experiences with simple and flexible blended education - Reitan, Janne Beate; Chaudhuri, Arnab (FormAkademisk, 2021)
This article presents an ongoing research project regarding blended education; Flexible Digital Classroom (FlexiDig), and a survey on full-time and part-time students’ experiences with blended education in a master’s degree programme in Art and Design Education. To optimise educational resources, the lectures for the full-time students were recorded, including the dialogue between the students and the lecturers, and made digitally available for all students. Generally, both the part- and full-time students participating in the questionnaire expressed their experience as “satisfactory” for the availability of the recorded lectures. Moreover, the capture of dialogues in the recording was found to be extremely useful for better understanding and learning, according to the students. This idea forms a basis to develop FlexiDig as simple as possible with a transfer value to other educational situations based on the approach of Student-Centered Learning and Teaching in Higher Education (SCLT).